ANALISIS FAKTOR- FAKTOR FINANCIAL DISTRESS FOOD AND BAVERAGE’S COMPANIES - Putri Dewi Permatasari; Totok Susilo Pamuji Nugroho (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to examine the effect of profitability, liquidity, leverage and growth ratio on financial distress in food and beverage companies listed on the Indonesia Stock Exchange in 2018 and 2019. This type of research is quantitative. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange in 2018 and 2019. The sample in this study used the purposive sampling method and obtained 10 food and beverage companies that matched the predetermined criteria. The data analysis technique used is multiple regression analysis with SPSS 16.0 program. The results showed that the liquidity and growth ratio variables had no effect on financial distress. While the profitability and leverage variables have an effect on financial distress.